2001
DOI: 10.1046/j.1439-0450.2001.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Prevalence of Riemerella anatipestifer in the Upper Respiratory Tract of Clinically Healthy Ducklings and Characterization of Untypable Strains

Abstract: A total of 44 bacterial strains obtained from 49 clinically healthy ducklings of different ages originating from four different farms were identified as members of the species Riemerella anatipestifer (RA) using conventional biochemical test methods. Numerical analysis of the whole-cell fatty acid patterns of these isolates resulted in two different clusters, one of which showed a similar pattern to that of the type strain of RA. Strains having a different fatty acid methyl esters (FAME)-profile (cluster II) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…Three duck species (Anatidae) had a 95% (71/75) prevalence in pharyngeal swabs. A similar result was reported in Pekin Duck (Anas platyrhynchos forma domestica) by Ryll et al (2001), who identified 39 RA from the pharynx of 49 Pekin Ducks and suggested that RA colonizes and persists on the pharyngeal mucous membranes of healthy domestic Pekin Ducks. Our findings indicate that RA might be common in the pharynx of wild ducks, as well as domestic ducks.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Three duck species (Anatidae) had a 95% (71/75) prevalence in pharyngeal swabs. A similar result was reported in Pekin Duck (Anas platyrhynchos forma domestica) by Ryll et al (2001), who identified 39 RA from the pharynx of 49 Pekin Ducks and suggested that RA colonizes and persists on the pharyngeal mucous membranes of healthy domestic Pekin Ducks. Our findings indicate that RA might be common in the pharynx of wild ducks, as well as domestic ducks.…”
Section: Discussionsupporting
confidence: 84%
“…None of the isolates grew on MacConkey's agar. The biochemical and physiologic properties were similar to those of type strain ATCC 11845 (Ryll et al 2001;Rubbenstroth et al 2011). …”
Section: Biochemical and Physiologic Characterizationsupporting
confidence: 60%
“…It is the causative agent of duck septicaemia (Segers et al, 1993), a contagious disease of domestic ducks, turkeys, and various other bird species. Duck septicaemia is a serious disease that has caused major economic losses for many duck farmers (Ryll et al, 2001;Sarver et al, 2005). Clinical signs include fibrinous pericarditis, perihepatitis, and airsacculitis.…”
Section: Introductionmentioning
confidence: 99%
“…anatipestifer is an avian pathogen of ducks and turkeys, and it is a major economic burden in the duck industry worldwide (Huang et al, 1999;Ryll et al, 2001;Pathanasophon et al, 2002;Sarver et al, 2002;Cheng et al, 2003). Limited information about the molecular basis of the pathogenesis is available for this organism, and so far only two potential bacterial virulence or virulence-associated gene have been identified (Weng et al, 1999;Crasta et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a contagious disease for domestic ducks, turkeys, and various other birds, and the disease can occur in an acute or chronic form of septicaemia, characterized by fibrinous pericarditis, perihepatitis, and airsacculitis. R. anatipestifer infection accounts for major economic losses for duck farmers (Sandhu & Rimler, 1997;Ryll et al, 2001;Sarver et al, 2002), especially in China and Southeastern Asia countries (Huang et al, 1999;Pathanasophon et al, 2002;Cheng et al, 2003). Such an infection causes high mortality and morbidity rates, typically ranging from 10% to 30% (Guo et al, 1982;Loh et al, 1992;Subramanism et al, 1997).…”
Section: Introductionmentioning
confidence: 99%